2014
DOI: 10.1039/c4lc00069b
|View full text |Cite
|
Sign up to set email alerts
|

Engineering interconnected 3D vascular networks in hydrogels using molded sodium alginate lattice as the sacrificial template

Abstract: Engineering 3D perfusable vascular networks in vitro and reproducing the physiological environment of blood vessels is very challenging for tissue engineering and investigation of blood vessel function. Here, we engineer interconnected 3D microfluidic vascular networks in hydrogels using molded sodium alginate lattice as sacrificial templates. The sacrificial templates are rapidly replicated in polydimethylsiloxane (PDMS) microfluidic chips via Ca⁺²-crosslinking and then fully encapsulated in hydrogels. Interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
145
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(148 citation statements)
references
References 35 publications
2
145
1
Order By: Relevance
“…Joshua Hammer et al [27] presented a process to fabricate hydrogels with microchannellike porosity in which stimuli-responsive calcium alginate microfilaments served as sacrificial materials for fluidic channels and were encapsulated within photocrosslinkable hydrogels composed of methacrylated gelatin (Gel-MA). Wang et al [28] described a method using a crosslinked sodium alginate as a biocompatible sacrificial template to fabricate interconnected 3D microfluidic vascular networks in hydrogels. The sacrificial templates are rapidly replicated in PDMS microfluidic chips via Ca 2þ -crosslinking, fully encapsulated in hydrogels, and then the interconnected 3D microfluidic channels were generated by dissolving the template with EDTA solution.…”
Section: Introductionmentioning
confidence: 99%
“…Joshua Hammer et al [27] presented a process to fabricate hydrogels with microchannellike porosity in which stimuli-responsive calcium alginate microfilaments served as sacrificial materials for fluidic channels and were encapsulated within photocrosslinkable hydrogels composed of methacrylated gelatin (Gel-MA). Wang et al [28] described a method using a crosslinked sodium alginate as a biocompatible sacrificial template to fabricate interconnected 3D microfluidic vascular networks in hydrogels. The sacrificial templates are rapidly replicated in PDMS microfluidic chips via Ca 2þ -crosslinking, fully encapsulated in hydrogels, and then the interconnected 3D microfluidic channels were generated by dissolving the template with EDTA solution.…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, it has been frequently discussed that the dissolving of sacrificial templates inside the cell-laden gel may hurt the cells. 29,31,33,50 However, continuous efforts until now have not yet fully addressed this common problem, probably because of the inherent drawback of the strategy that involves microfabrication process in the presence of the live cells. For instance, in a recent report, Huang and his co-workers tried to reduce the damage to cells caused by the fabrication process by using a biocompatible sacrificial template made of sodium alginate; however, the reagent used for dissolving the template, ethylenediaminetetraacetic acid (EDTA), is not biocompatible.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in a recent report, Huang and his co-workers tried to reduce the damage to cells caused by the fabrication process by using a biocompatible sacrificial template made of sodium alginate; however, the reagent used for dissolving the template, ethylenediaminetetraacetic acid (EDTA), is not biocompatible. 50,51 In another work, Chen et al reported a smart design using a 3-D-printed carbohydrate glass sacrificial template that dissolves in water; however, although this template can be removed by a biocompatible buffer, the dissolution of carbohydrate will cause osmotic shock that damages the cells. 31 Thus, the authors needed to coat the carbohydrate glass lattice with a thin layer of poly(D-lactide-co-glycolide) (PDLGA); and because the template was highly hygroscopic, it had to be reinforced by dextrans, and stored at 45 C or in a vacuum chamber before use.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations